Fluid‐assisted deformation of the subduction interface: Coupled and decoupled regimes from 2‐D hydromechanical modeling. Issue 8 (12th August 2016) - Zheng, Liang; May, Dave; Gerya, Taras; Bostock, Michael
Abstract: Shear deformation, accompanied with fluid activity inside the subduction interface, is related to many tectonic energy‐releasing events, including regular and slow earthquakes. We have numerically examined the fluid‐rock interactions inside a deforming subduction interface using state‐of‐the‐art 2‐D hydromechanical numerical models, which incorporate the rock fracturing behavior as a plastic rheology which is dependent on the pore fluid pressure. Our modeling results suggest that two typical dynamical regimes of the deforming subduction interface exist, namely, a "coupled" and a "decoupled" regime. In the coupled regime the subduction interface is subdivided into multiple rigid blocks, each separated by a narrow shear zone inclined at an angle of 15–20° with respect to the slab surface. In contrast, in the decoupled regime the subduction interface is divided into two distinct layers moving relative to each other along a pervasive slab surface‐parallel shear zone. Through a systematic parameter study, we observe that the tensile strength (cohesion) of the material within the subduction interface dictates the resulting style of deformation within the interface: high cohesion (~60 MPa) results in the coupled regime, while low cohesion (~10 MPa) leads to the decoupled regime. We also demonstrate that the lithostatic pressure and inflow/outflow fluid fluxes (i.e., fluid‐fluxed boundary condition) influence the location and orientation of faults. Predictions from our numerical models are supported by experimental laboratory studies, geological data, and geophysical observations from modern subduction settings. Key Points: Shear deformation triggers fluid‐rock interaction and localized fluid migration Coupled and decoupled fracturing modes exist in the subduction interface Tensile strength controls the fracturing modes